El problema de la teodicea en el pensamiento de Joseph de Maistre - Andrade, Gabriel Ernesto (’Ilu. Revista de Ciencias de las Religiones, 2006)
The problem of theodicy has been one of the greatest worries of religious thought in the West: if God is absolutely good and omnipotent, how can evil exist in the world, and why do the virtuous suffer while the corrupt enjoy? In Antiquity, the Book of Job tried to offer a response that had influence until modern times. In the XVII Century, Leibniz offered a much more rationalized answer, proper for modernity. Joseph de Maistre, a counter-revolutionary of the XIX Century, took theodicy as one of his central themes. This article is a study of the way that De Masitre approaches this issue.